Investigating the Potential of Aquaponics to Increase Food Production and Reduce Environmental Impact - Husain Saif O.; Abed Z.; Raju Y. Kamala (SHS Web of Conferences, 2025)
Traditional agricultural techniques struggle to meet the requisite sustainability and resource efficiency requirements with the growing demand for global food supply. High water usage, degradation of the soil and excessive energy usage are becoming pressing. This study seeks binary solutions to these challenges and the potential improvement to food production methods with aquaponics, or an integration of aquaculture with hydroponics. What is causing the problem is the desire to come up with a more eco and resource friendly agricultural technique to accommodate the increase in food consumption but at the same time, causing minimal environmental damage. One has the limitations of their environmental footprint which conventional methods such as soil-based farming and hydroponics have (in terms of water usage and nutrient recycling). In this context, the aquaponics system is proposed since it combines fish farming and plant cultivation in a closed loop. It uses fish waste as nutrients for plants that in turn filter out and purify the water for the fish. Aquaponics is compared to other methods such as hydroponics, traditional soil-based farming, vertical farming, aeroponics, among other methods of farming. Results indicate that aquaponic systems have a superior resource efficiency compared to other methods and achieve lower water and energy consumptions. It further shows high competitiveness of crop yields, and less environmentally impacting solution for future sustainable food production.